2015
DOI: 10.1097/aap.0000000000000223
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Spine and Pain Procedures in Patients on Antiplatelet and Anticoagulant Medications

Abstract: Interventional spine and pain procedures cover a far broader spectrum than those for regional anesthesia, reflecting diverse targets and goals. When surveyed, interventional pain and spine physicians attending the American Society of Regional Anesthesia and Pain Medicine (ASRA) 11th Annual Pain Medicine Meeting exhorted that existing ASRA guidelines for regional anesthesia in patients on antiplatelet and anticoagulant medications were insufficient for their needs. Those surveyed agreed that procedure-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
72
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(74 citation statements)
references
References 400 publications
(433 reference statements)
0
72
0
2
Order By: Relevance
“…3 We agree that the interruption of DOACs should not be based only on their respective half-life but also on the residual drug concentration. Indeed, a recent multicenter study showed a high interindividual variability of DOACs' plasma concentration.…”
mentioning
confidence: 76%
“…3 We agree that the interruption of DOACs should not be based only on their respective half-life but also on the residual drug concentration. Indeed, a recent multicenter study showed a high interindividual variability of DOACs' plasma concentration.…”
mentioning
confidence: 76%
“…While there are other documented case reports of epidural hematoma formation following ILESI in patients that have followed current guidelines for the discontinuation of antiplatelet and anticoagulation medications, there are two factors that we feel make our case unique 1–4. First, even though the ASRA guidelines published by Narouze et al in 2015 were largely followed in this patient, she was later discovered to have regularly taken 2000 mg of fish oil daily and ibuprofen 400 mg as needed 5. In April 2018, Narouze et al published the second edition of the ASRA guidelines for interventional spine and pain procedures.…”
Section: Discussionmentioning
confidence: 97%
“…Recent ASRA and ESRA consensus indicates a 3–4 days interval before performing regional anesthesia procedures and then resuming medications 12–24 h postprocedure. [14]…”
Section: Factor Xa Inhibitorsmentioning
confidence: 99%
“…[1417] As experience with this agent is limited, along with wide-ranging pharmacokinetics of apixaban therapy, it is warranted to delay postprocedure administration by 6 h.[1419]…”
Section: Factor Xa Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation